Mysid meal as a dietary replacement for fishmeal in the diets of Pacific white shrimp Penaeus vannamei (Boone, 1931) postlarvae - Andam, Michael B.; Traifalgar, Rex Ferdinand M.; Laureta, Liberato V.; Nuñal, Sharon N.; Nillos, Mae Grace G. (Frontiers in Sustainable Food Systems, 2024)
The current study evaluates the nutritional and feed value of mysid meal (MM) as a substitute for fishmeal (FM) in the Pacific white shrimp (Penaeus vannamei) postlarvae diet. Five experimental diets were formulated by replacing 0 (MM0), 25 (MM25), 50 (MM50), 75 (MM75), and 100 % (MM100) of dietary FM with MM. These experimental feeds were fed to P. vannamei postlarvae in a 60-day feeding trial. Results revealed that MM could entirely substitute 100 % FM in the white shrimp diet. Furthermore, results showed that 75 % FM replacement with MM elicited a growth-enhancing effect and improved feed nutrient utilization. No significant treatment effects were detected in the survival, total feed intake, and biochemical body composition of P. vannamei. The observed improvement in shrimp growth in terms of weight gain (WG), specific growth rate (SGR), and nutrient retention were positively correlated with the substitution level of FM by MM. The feed conversion ratio (FCR) was negatively correlated with the substitution of MM and with the growth indices including WG and SGR. In conclusion, 100% of the FM (40% in the control diet) can be substituted by dietary MM without affecting the survival, growth, feed utilization, and biochemical carcass composition of P. vannamei. Polynomial regression analysis of SGR indicates that 65.50% of MM is optimum to replace FM in the diet of P. vannamei to attain maximum growth.